THE INFLUENCE OF ORGANIZATIONAL CLIMATE, EFFECTIVE COMMUNICATION, AND COMPENSATION ON NURSE PERFORMANCE AT RS. SENTRAL MEDIKA KARAWANG - Ferry Victor; Muhammad Fachruddin Arrozi; Rokiah Kusumapradja (CV. Bunda Ratu, 2024)
Quality nursing care has a direct impact on hospital performance, one of which is influenced by the performance of nurses. Nurse performance is essentially the result of a nurse's work over a specific period based on predetermined and agreed-upon standards, targets, or criteria. This research uses a quantitative approach with a causal research design using Multiple Regression Analysis with the assistance of SPSS. The sample in this study consisted of 50 nursing staff working in all service units of RS Sentral Medika Karawang. The research instrument used a questionnaire and was measured using a Likert scale. Research Results: There is a significant influence of organizational climate, effective communication, and compensation on performance at RS Sentral Medika Karawang (f count > f table (216.013>2.794) and significance (p-value) 0.000<0.05). Implications and Suggestions: There is a need to create and improve the Good Hospital Good Governance system, interprofessional profession correlation or interprofessional collaboration system, and meritocracy system in compensation delivery to improve motivation and employee performance, thereby enhancing the quality and efficiency of RS Sentral Medika Karawang activities. Keywords: Organization Climate, Effective Communication, Compensation, Performance, Nurse